Lighting Evaluation and Optimization of Lamp Placement in the Nursing Research Centre Classrooms at Universitas Muhammadiyah Semarang - Abdul Rohman (Faculty Of Engineering University 17 August 1945 Semarang, 2022)
Adequate lighting in a classroom is characterized by the ability to see objects clearly and comfortably without creating shadows. Lighting can be sourced naturally from sunlight and artificially from lamps. Natural lighting is only available during the day, necessitating artificial lighting during overcast weather or nighttime. The Nursing Research Centre (NRC) classrooms at Universitas Muhammadiyah Semarang (Unimus) are heavily used, requiring sufficient lighting to meet standards. This study aims to measure the quality of lighting in the NRC classrooms at Unimus and determine whether it meets the established standards. The study was conducted in the NRC classrooms at Unimus, using lighting evaluation methods based on SNI 6197: 2011and SNI 6197: 2020. The evaluation results indicate that the lighting levels in the NRC classrooms do not meet the standards, with an average illumination of only 200 lux. The study recommends replacing the existing lamps with 2x24 watt LED lamps with 2x2800 lumens, and the need for small electrical power so that it os more efficient.